The Effect of Profitability, Capital Structure, and Total Asset Turnover on Company Value with Dividends as a Moderating Variable - Talitha Azka Zafarini; Maretha Ika Prajawati (Universitas Nusantara PGRI Kediri, 2026)
With dividend policy acting as a moderating variable, this study attempts to examine the effects of profitability, capital structure, and total asset turnover on firm value. The study employs an associative research design and a quantitative methodology. 310 businesses from the consumer staples, industrial, and materials industries that were listed on the Indonesian Stock Exchange between 2020 and 2024 make up the population. 39 businesses satisfied the research criteria based on a selective sampling selection, and following data cleaning with case diagnostics, 192 observations were obtained. The Statistical Package for the Social Sciences (SPSS) was used to examine secondary data that was taken from the yearly financial statements of businesses. The following metrics are used to quantify: return on assets, debt to equity ratio, total asset turnover, Tobins Q, and dividend payout ratio. The findings indicate that business value is significantly impacted by profitability, capital structure, and total asset turnover. Additionally, the relationship between profitability and company value can be moderated by dividend policy, but the impact of capital structure and total asset turnover on firm value cannot be moderated. These results suggest that while dividend policy has a selective moderating effect, financial performance is a significant factor in raising firm value.